Landfill Management, Leachate Generation, and Leach Testing of Solid Wastes in Australia and Overseas - SCOTT, JASON; BEYDOUN, DONIA; AMAL, ROSE; LOW, GARY; CATTLE, JULIE (Critical reviews in environmental science and technology, 2005)
Disposal of waste to landfill remains the most common means of waste management worldwide. The most serious environmental impact of waste disposal to landfill is contamination of local groundwater by the generated leachate. One measure designed to prevent this occurring is the classification of the nature of the waste (hazardous or nonhazardous) in order to determine the most appropriate means of disposal. Of the numerous tests developed to classify solid waste, the toxicity characteristic leaching procedure (TCLP) is the most commonly used in Australia. This test was developed in the United States. Since its dissemination, the TCLP has been subject to extensive scrutiny regarding its effectiveness as a compliance tool for waste classification, particularly in view of the advances in waste management practices over the past decade. Within Australia, concerns also exist regarding its applicability for Australian conditions. This review on landfill practices and waste classification found the TCLP to be limited in its usefulness as a regulatory tool within Australia. Moreover, this review identified various gaps in the knowledge pertaining to landfills, leachate generation, and waste classification that necessitate action to improve waste management practices in the future.